Cuttlefish culture: state of art and future trends - Sykes, António V. (2018)
The present article provides an overview of cuttlefish culture, its current state of art, and future trends. Present cuttlefish culture related research, recently developed technologies (like culture systems, maternity/nursery and juvenile and adult proceedings) are described. Finally, current problems and prospects for future research are discussed.